Genomic conservation and putative downstream functionality of the phosphatidylinositol signalling pathway in the cnidarian-dinoflagellate symbiosis - Ashley, Immy A.; Kitchen, Sheila A.; Gorman, Lucy M.; Grossman, Arthur R.; Oakley, Clinton A.; Suggett, David J.; Weis, Virginia M.; Rosset, Sabrina L.; Davy, Simon K. (Frontiers in Microbiology, 2023)
The mutualistic cnidarian–dinoflagellate symbiosis underpins the evolutionary success of stony corals and the persistence of corals reefs. However, a molecular understanding of the signalling events that lead to the successful establishment and maintenance of this symbiosis remains unresolved. The phosphatidylinositol (PI) signalling pathway has been implicated during the establishment of multiple symbiotic and parasitic interactions across the kingdom of life, yet its role within the cnidarian-algal symbiosis remains unexplored. Here, we compiled 21 symbiotic anthozoan (corals and sea anemones) and 28 symbiotic dinoflagellate (Symbiodiniaceae) transcriptomic and genomic datasets and queried genes related to the PI signalling pathway. Presence or absence of PI-kinase and PI-phosphatase orthologs were compared between a broad sampling of taxonomically-related symbiotic and non-symbiotic species. Across the symbiotic anthozoans analysed, there was a complete and highly conserved PI pathway, analogous to the pathway found in model eukaryote organisms. The Symbiodiniaceae pathway showed similarities to its sister taxon, the Apicomplexa, with the absence of PI 4-phosphatases. However, conversely to Apicomplexa, there was also an expansion of homologs present in the PI5-phosphatase and PI5-kinase groups, with unique Symbiodiniaceae proteins identified that are unknown from non-symbiotic unicellular organisms. Analysis of phosphoinositide (PIP)-binding proteins showed that, on average, 2.23% and 1.29% of the total assemblies were identified in the anthozoan and Symbiodiniaceae assemblies, respectively, with the potential to bind to phosphoinositides. Enrichment of Gene-Ontology (GO) terms associated with predicted PIP-binding proteins within each taxon revealed a broad range of functions, including compelling links to functionality within the symbiosis. This analysis establishes a baseline for current understanding of the PI pathway across anthozoans and Symbiodiniaceae, and thus a framework to target future research.